The Effect of Tui Na Massage on Sleep Quality of 4-5 Years Old Toddlers in an Efforts to Prevent Stunting in Banjar Kawan, Bangli - Bella Krisna Pramitha; Ni Luh Gede Intan Saraswati; Ni Putu Wiwik Oktaviani; Ni Komang Ayu Resiyanthi (Future Science, 2024)
Introduction: One factor that can contribute to stunting is poor sleep quality in children. This is due to the disruption of the growth hormone process, which can lead to shorter stature. The aim of this research was to determine the effect of Tui Na massage on the sleep quality of toddlers aged 4 to 5 years.Method: This research employed a quantitative pre-experimental design with a one-group pre-test and post-test structure. It involved 34 respondents, selected using a purposive sampling technique. Tui Na massage was the intervention applied. The Pittsburgh Sleep Quality Index (PSQI) questionnaire was used to measure sleep quality.Results: Before the Tui Na massage, the majority of toddlers had sleep quality categorized as poor, with 16 respondents (47.1%). After six consecutive days of Tui Na massage, the toddlers' sleep quality im-proved, with 24 respondents (70.6%) showing better sleep quality. Da-ta analysis using the Wilcoxon Signed Rank Test yielded an Asymp. Sig. (2-tailed) value of -4.969 with a p-value of 0.000, indicating a statisti-cally significant effect of Tui Na massage on the sleep quality of toddlers in efforts to prevent stunting in Banjar Kawan, Bangli.Discussion: Good quality sleep in toddlers is essential for support-ing optimal growth and development, which can help reduce the risk of stunting.